DİL VE EDEBİYAT YÖNÜNDEN HZ.PEYGAMBER VE HULEFÂ-İ RÂŞİDÎN - Tacettin Uzun (İstem, 2005)
Prophet Muhammad and al-Khulafa al-Rashidun from the Language and Literature Point of View Language and literature are two of the significant ranks hold by the four caliphs who became famous as "al-Khulafa al-Rashidun". As a matter of fact, talkings and writings determine one’s position in language and literature. In this article, by examining their khutbahs and correspondences, al-Khulafa al-Rashidun's position in language and literature has been attempted to be identified